A comparison of two different dosages of conjugated equine estrogen in continuous combined hormone replacement therapy with progestin - 邢淑敏 吴宜勇 刘建立 徐茹兰 张忠兰 王莹 (Chinese medical journal, 2003)
Objective To investigate the effects of two different dosages of conjugated equine estrogen (CEE)on preventing bone loss and relieving the symptoms of menopausal syndrome in women at an early stage of menopause.Methods A total of 236 postmenopausal women were randomly allocated to one of the following groups: Group A: 0. 625 mg CEE +2 mg medroxyprogesterone acetate (MPA) +1 tab Caltrate-D per day; Group B: 0.3 mg CEE +2 mg MPA +1 tab Caltrate-D per day; Group C. 1 tab Caltrate-D per day as the control group. The study was continued for 2 years. The following parameters were monitored:①L2-4 bone mineral density (BMD) (measured with dual energy X-ray absorptiometry(DEX)), ② menopausal syndrome improvement (assessed by comparing Kupperman scores),③vaginal bleeding rate, and the thickness of the endometrium and breast in each group.Results Overall, 213 cases (90%) completed the 1-year study and 176 cases (75%) completed the 2-year study. The percentage changes in L2-4 BMD at the 12th and 24th month in Group A were+2. 3% and + 3. 7%, respectively, with the posttreatment values being significantly higher than pretreatment values ( P<0. 001 ). The percentage changes were +2. 7% at 12th month ( P <0. 05)and +0. 7% at 24th month (P>0. 05) in Group B. And that of Group C were -0.4% at 12th month and - 1.6% at 24th month ( P >0.05). L2-4 BMD in both Group A and B was significantly higher than that in Group C at 12th and 24th month (A vs C, P<0. 001 ; B vs C, P<0.05). Kupperman Scores were significantly reduced after 1, 3, 6 , 12 and 24 months in all 3 groups when compared with baseline ( P <0. 001 ). Scores in Group A and Group B were significantly lower than that in Group C (P<0. 001 ). However, the vaginal bleeding rates in Group A were significantly higher than that in Group B or in Group C. There was no atypical hyperplasia of endometrium in the 3 groups by the end of the study. One patient in Group A developed superficial thrombophlebitis by the end of 12th month.Conclusion Continuous combination of CEE and MPA is effective in preventing bone loss and relieving the symptoms of menopausal syndrome in women at an early stage of menopause. The vaginal bleeding rates in the Group treated with 0. 625 mg/d CEE were significantly higher than those treated with 0.3 mg/d CEE.